2014
DOI: 10.1021/jz500222f
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Redox Mediators for Enhancing Utilization of Li2S Cathodes for Advanced Li–S Battery Systems

Abstract: The development of Li2S electrodes is a crucial step toward industrial manufacturing of Li-S batteries, a promising alternative to Li-ion batteries due to their projected two times higher specific capacity. However, the high voltages needed to activate Li2S electrodes, and the consequent electrolyte solution degradation, represent the main challenge. We present a novel concept that could make feasible the widespread application of Li2S electrodes for Li-S cell assembly. In this concept, the addition of redox m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(215 citation statements)
references
References 16 publications
2
212
0
1
Order By: Relevance
“…Organometallic redox mediators are shown to provide better utilization of Li 2 S (ref. 34). Additives such as P 2 S 5 also effectively control Li 2 S deposition and aid in elimination of the polysulfide shuttle 35 .…”
mentioning
confidence: 99%
“…Organometallic redox mediators are shown to provide better utilization of Li 2 S (ref. 34). Additives such as P 2 S 5 also effectively control Li 2 S deposition and aid in elimination of the polysulfide shuttle 35 .…”
mentioning
confidence: 99%
“…Figure 2d shows that the redox reaction of SiW itself contributed only slightly to the cell capacity, confirming the role of the POM as a mediator. While some organometallic compounds have previously shown mediation effects for the charging process, 6 it is here demonstrated that Keggin-type POMs improve the capacity as redox mediators for both charging and discharging reactions and allow long-term cycling performance in Li-S cells without any physical modification of the carbon supports.…”
Section: ¹1mentioning
confidence: 63%
“…The cathode electrolytes consisted of 10 µL of sulfolane containing 10 mM of the relevant POM and 1 M LiTFSI, as sulfolane allowed stable operation at high temperatures due to its high boiling point (>280°C) while ether-based liquid electrolytes would not. 6,12,[21][22][23][24][25] Hence, each cell contained 0.1 µmol of POM and approximately 28 µmol of sulfur atoms. A standard electrolyte that did not contain POM was also used as a control sample.…”
Section: Cell Preparation With Protective Anodementioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] Those consisting of polycyclic aromatic hydrocarbons, and in particular perylene bisimide 44,45 (PBI) and benzo[ghi]perylene imide (BPI), as reported by us, are amenable to supramolecular polymerization via π-stacking. Whereas our previous accounts focused on the action of soluble redox mediators in Li-S cells, our focus here is instead on their action in the solid state as a binder.…”
Section: Resultsmentioning
confidence: 99%